Consumer protection laws and your businesses - Amin, Naemah (2012)
The presentation aims to inform businesses of various consumer protection laws in Malaysia, in particular the laws under the jurisdiction of the Ministry of Domestic Trade,Cooperatives and Consumerism. It specifically focusses on understanding business’ obligations under the Consumer Protection Act 1999. It also highlights the recent amendment and development of the law and its implication on business activity.